THU0611 SERUM HIGHLY-SENSITIVE CARDIAC TROPONIN-I AND ANTI-BETA2-GLYCOPROTEIN-1 IGA ANTIBODIES AT BASELINE PREDICT CORONARY PLAQUE PROGRESSION IN RHEUMATOID ARTHRITIS. (June 2019) - Karpouzas, George; Ormseth, Sarah; Hernandez, Elizabeth; Estis, Joel; Todd, John; Budoff, Matthew
Abstract : Background: We recently reported that serum levels of highly-sensitive cardiac troponin-I (hs-cTnI)- a specific structural myocardial biomarker- associated with occult coronary plaque presence, burden and long-term cardiovascular events in patients with rheumatoid arthritis (RA). We further demonstrated that presence of IgA antibodies against beta2-glycoprotein-1 (a-b2GPI-IgA, an apolipoprotein readily expressed in human atherosclerotic plaque) associated with baseline coronary artery calcium (CAC) scores and independently predicted CAC progression in patients with RA. Objectives: We here explored whether baseline evaluation of both hs-cTnI and a-b2GPI-IgA better predicts CAC progression than either of them in isolation. Methods: Ninety five participants with a baseline plaque evaluation by coronary computed tomography angiography (CCTA) underwent follow-up assessment within 6.9±0.3 years. Coronary artery calcium (CAC) was quantified by the Agatston method. Hs-cTnI and a-b2GPI IgA Ab were assessed on the day of baseline CCTA; the latter were reconfirmed 12 weeks later, if positive. CAC change was evaluated with the MESA method as the natural logarithm plus 25 difference [(ln CAC(follow-up) + 25) – (ln CAC(baseline) + 25)]. Generalized linear models evaluated the effect of hs-cTnI, a-b2GPI-IgA and their interaction on CAC change. Models were adjusted for age, hypertension, waist-to height ratio (obesity indicator), cumulative inflammatory burden (time-averaged C-Reactive protein), total prednisone dose and duration of statin exposure from baseline to follow-up scan. Results: Baseline hs-cTnI was higher in a-b2GPI-IgA positive compared to negative patients [median (IQR) of 1.9 (1.6-2.6) vs. 1.4 (1.3-1.7) respectively, p=0.043]. Hs-cTnI alone did not independently predict CAC change (β=0.214, p=0.132) in the multivariable model whereas a-b2GPI-IgA presence did (β=0.454, p=0.003). There was a significant interaction between hs-cTnI and a-b2GPI-IgA on CAC progression (Wald Chi-square=4.19, p=0.041); high hs-cTnI (>1.5pg/ml) predicted significantly greater CAC change in a-b2GPI-IgA positive patients but not in negative ones [estimated marginal mean difference (IQR)=0.36 (0.12-0.59), p=0.003) and figure 1 ]. Conclusion: Baseline hs-cTnI in isolation is not predictive of CAC progression in patients with RA; however, in the context of a-b2GPI-IgA presence, high hs-cTnI independently predicts significant increase in coronary atherosclerosis burden. Disclosure of Interests: George Karpouzas Grant/research support from: Pfizer, Consultant for: Sanofi-Genzyme-Regeneron, Janssen, Roche-Genentech, Pfizer, Speakers bureau: BMS, Sanofi-Genzyme-Regeneron, Janssen, Roche-Genentech, Sarah Ormseth: None declared, Elizabeth Hernandez: None declared, Joel Estis Employee of: Singulex, John Todd Employee of: Singulex, Matthew Budoff: None declared